The Second Generation from Sun Myung Moon’s Unification Movement and Their Multiple Cohorts - Chiaia, Nicholas (International journal for the study of new religions, 2022)
This study updates explanations about the late Reverend Dr. Sun Myung Moon’s ("Reverend Moon") Unification Movement, a new religious movement he founded in 1954. The Unification Movement substantively fragmented, beginning in 2008 following the founder’s age-related mental and physical decline. This study principally focuses on the Unification Movement Second Generation, and it provides critical detail about the Movement’s financial dimension and its impact on the Second Generation in Japan. It also differentiates Unification Movement Second Generation into three cohorts: the pre-hometown nursery cohort, the Japanese cohort, and the hometown cohort, noting the varying sociological outcomes of each of these three distinct groups.